THE PRINCIPLE AND THE METHOD OF FINDING OUT THE CUBE ROOT OF ANY NUMBER - Trivedi, S.K. (SCHOOL SCIENCE, 2013)
The two methods usually employed to find the cube root of a number are, (i) the method of factorisation, and (ii) the division method. However, it is the method of factorisation that generally finds a place in the school mathematics to obtain the cube root of a number. It may be pointed that this method is convenient to find cube root of the numbers that are a perfect cubes. Here an attempt has been made to explain the method to find the cube root of any number by the method of division. The advantage of this method over the method of factorisation is that it is possible to find the cube root of any number up to the desired decimal places.